Comparative Analysis of the Expression of Genes Involved in Fatty Acid Synthesis Across Camelina Varieties - Elisa Gómez; Gregorio Hueros; David Mostaza-Colado; Aníbal Capuano; Mercedes Uscola; Pedro V. Mauri (Agriculture)
Camelina sativa (L.) Crantz, a native European oilseed crop of the Brassicaceae family, is notable for its short life cycle, making it well-suited for crop rotation and diversification. Its seeds contain a high content of oil (36–47%) that is rich in polyunsaturated fatty acids (PUFAs) such as alpha-linolenic acid (ALA, C18:3, Ω-3) and linoleic acid (LA, C18:2, Ω-6). This oil has diverse industrial applications, including low-emission biofuels, animal feed, pharmaceuticals, biolubricants, bioplastics, and cosmetics. We analyzed the expression of seven key enzymes involved in fatty acid biosynthesis across nine C. sativa accessions at three stages of silique development using highly efficient qRT-PCR assays designed for the target genes and a normalizing control. Our detailed expression analysis revealed significant variation across varieties, with only the gene FAB2c exhibiting genotype-independent expression, indicating a constitutive and essential role in monounsaturated fatty acid (MUFA) biosynthesis. Other genes showed significant interactions between the variety and developmental stage, highlighting the combined influences of genetic background and silique maturation on gene regulation. V18 emerges as particularly promising, exhibiting elevated expression of genes linked to PUFA and VLCFA biosynthesis—traits of significance for food, biofuel, and industrial applications. These findings, together with the developed qRT-PCR assays, provide valuable tools for selecting Camelina varieties with optimized genetic profiles, highlighting the potential of harnessing natural transcriptional diversity for crop improvement.